2010
DOI: 10.1158/1541-7786.mcr-10-0089
|View full text |Cite
|
Sign up to set email alerts
|

Xrcc2 Modulates Spontaneous and Radiation-Induced Tumorigenesis in Apcmin/+ Mice

Abstract: XRCC2 has an important role in repair of DNA damage by homologous recombination. Adult Apc min/+ (min, multiple intestinal neoplasia) mice, wild-type or heterozygous for Xrcc2 deficiency, were sham-irradiated or 2-Gy X-irradiated. Spontaneous mammary and intestinal tumor incidences are lower in Apc min/+ Xrcc2 +/− mice than in Apc min/+ Xrcc2 +/+ mice (mammary tumors: 14% and 38%, respectively, χ 2 P = 0.03; intestinal adenomas in mice reaching full life span: 108.6 and 130.1, respectively, t-test P = 0.005). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…A recent study showed that the incidence of spontaneous breast and intestinal tumorigenesis was higher in XRCC2 +/+ mice than in XRCC2 +/− animals [22], implicating a possible role for XRCC2 in affecting tumor cells’ radiosensitivity. In the present study, we found that the expression of XRCC2 protein was elevated in colon cancer cells compared with normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the incidence of spontaneous breast and intestinal tumorigenesis was higher in XRCC2 +/+ mice than in XRCC2 +/− animals [22], implicating a possible role for XRCC2 in affecting tumor cells’ radiosensitivity. In the present study, we found that the expression of XRCC2 protein was elevated in colon cancer cells compared with normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that genes such as Prkdc and Xrcc2, involved in the non-homologous end joining and homologous recombination repair pathways, respectively, modify radiation cancer risk in mouse models, and there is a degree of tissue specificity (e.g. Degg et al, 2003;Haines et al, 2010Haines et al, , 2015. Although DNA repair genes have not been commonly identified in screens for radiation cancer risk modifiers, some repair-related genes have been found to modify risk in humans, most notably in the case of ATM and radiogenic breast cancer (e.g.…”
Section: Molecular and Cellular Biological Considerationsmentioning
confidence: 99%
“…However, when crossed with the APCmin mouse model, Haines et al found that Xrcc2 modifies the impact of APC mutagenesis [53]. These data are interesting, though not inconsistent with the above described studies, in that the effect of Xrcc2 gene dosage (i.e., protective or detrimental) depends upon the specific experimental conditions.…”
Section: Deans Et Al Established Es Cells Frommentioning
confidence: 78%
“…These data are interesting, though not inconsistent with the above described studies, in that the effect of Xrcc2 gene dosage (i.e., protective or detrimental) depends upon the specific experimental conditions. Xrcc2 heterozygosity protects from the spontaneous intestinal tumorigenesis induced by the APC mutation, but enhances IR-induced tumorigenicity in this same APC model [53]. It is difficult to reconcile such data without further experimental evidence.…”
Section: Deans Et Al Established Es Cells Frommentioning
confidence: 99%